The Effectiveness of ChatGPT on Students` Writing Ability at Indonesian Classroom - Ayu Sri Rezeky; Lainatusshifa Saragih; Tifani Fadhillah; Sholihatul Hamidah Daulay (Universitas Negeri Islam Sumatera Utara, 2025)
This study aimed to determine the effect of using ChatGPT on students' writing skills, especially simple sentences in English. The background of this study is based on students' still low ability to write sentences with correct structure and grammar, especially in the use of Simple Present Tense. This study used a quantitative approach with a quasi-experimental design of the pretest-post-test control group design. The research sample consisted of two eighth grade classes at MTsS YMPI Tanjungbalai, namely class VIII-1 as the experimental class learning using ChatGPT and class VIII-2 as the control class learning using conventional methods, each consisting of 30 students. Data were collected through writing tests given before and after the treatment. The results of the analysis showed that the average post-test score of the experimental class was higher than the control class, and the t-test produced a significance value of 0.000 <0.05. This indicates a significant difference between the two groups. Thus, it can be concluded that the use of ChatGPT has a positive and significant effect on improving students' ability to write simple English sentences, especially in understanding the basic structure of Subject-Verb-Object and the application of Simple Present Tense.